Performance of three racial groups of grazing steers supplemented with agroindustrial by-products - Mestra-Vargas, Lorena Inés (2020)
Performance of three racial groups of grazing steers supplemented with agroindustrial by-products. The main objective of this research was to evaluate the productive performance of three racial groups of steers, receiving or not supplementation with agro-industry by-products under grazing conditions in the humid Colombian Caribbean. Forty-eight steers: Angus x Brahman (AxB), Simmental x Brahman (SxB) and Romosinuano x Brahman (RxB) with average weight of 274± 13,76 kg and 17 months old  were randomly distributed to two types of feed management; with feed supplementation (CSA: 24 animals) and without  feed supplementation (SSA: 24 animals) in each breed group, using a complete randomized design (DCA). The supplementation consisted of a mix of rice bran (56.5%), cottonseed (43.5%) and mineralized salt (100 g/steer/day). The highest daily weight gain (GDP) was observed in the animals of the treatments AxB CSA, SxB CSA and RxB CSA (p= 0.001) with 730, 942 and 650 g/day respectively. The GDP of the animals AxB SSA, SxB SSA and RxB SSA, corresponded to  560, 520, and 608 g/animal/day. Regarding body composition by ultrasound measurements, the greater attributes of the ribeye area (p=0.0175) were observed for the AxB CSA (43.73 2.54 cm2) y RxB CSA treatments (45,51±2,34 cm2) and for the rump fat thickness (p=0.0229), the RxB CSA treatment (3.97 0.25 mm). The highest projected meat production kg/ha in a year, corresponded to the average for the biotypes of CSA treatment with 1,131.33 kilograms/ha/year, surpassing by 27.5% the production of SSA biotypes treatment of 821.26 kilograms. From  the results obtained in this research, the supplementation of grazing steers with by-products of agro-industry  becomes a productive activity to increasing GDP and meat production kg/ha, reflecting the potential of this practice as a valid strategy for the development of more efficient and competitive meat production systems for the humid Colombian Caribbean region.